Membaca Lancar Level I Siswa Kelas I SD - Melsi Wulandari; Chandra Chandra; Salmaini Safitri Syam (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This study aims to assess the fluency reading skills of first-grade elementary school students, focusing on pronunciation accuracy, reading smoothness, use of intonation, and reading independence. A descriptive qualitative approach was used, with data collected through observations, interviews, reading assessments, and supporting documentation. The findings reveal varied reading abilities among students; some demonstrate good fluency and independence, while others struggle with pronunciation, flow, and expression. These results highlight the need for appropriate teaching methods and active involvement of both teachers and parents to improve early reading skills. This research provides a foundation for developing effective reading instruction strategies to support students' academic progress in the future.